Microstructural Characterization and Microhardness Analysis of A356 and AC2B Aluminium Alloys Subjected to T6 Artificial Ageing Heat Treatment - Cunha, Joziane Silva da (2025)
Aluminum is the third most abundant metal in the earth's crust and is widely used in the automotive, aerospace and scientific research industries due to its properties such as lightness, mechanical and corrosion resistance. The aim of this work was to comparatively analyze the microstructures of aluminum alloys A356 and AC2B after T6 artificial aging heat treatment. The samples were solubilized at 400 ± 5 °C for 6 hours, followed by aging at 140 °C and 160 ± 5 °C, with time variations. The samples were cooled to room temperature. Characterization methods such as metallography, macro and microstructural analysis, microhardness testing and optical microscopy were used. The results showed that the variation in ageing time and temperature directly influenced the microhardness of the alloys, improving their mechanical properties. It is concluded that the T6 treatment contributes to improving the structural performance of the alloys and is effective for applications requiring greater strength and reliability